2006
DOI: 10.1089/vim.2006.19.189
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine and C-Reactive Protein Profiles Induced by Porcine Circovirus Type 2 Experimental Infection in 3-Week-Old Piglets

Abstract: The purpose of this study was to determine serum profiles of cytokines at a protein level and Creactive protein (CRP) during the development of postweaning multisystemic wasting syndrome (PMWS) in experimentally inoculated pigs. Levels of serum IFN-alpha, IL-6, IL-10, and CRP were examined for a 35-day period in 10 piglets experimentally infected with PCV2 at 3 weeks of age. Four of the infected piglets developed severe PMWS at 14 to 21 days post-infection (d.p.i.) and died prior to termination of the experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
29
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(34 citation statements)
references
References 26 publications
5
29
0
Order By: Relevance
“…Many studies have revealed that the induction of IL-10 upregulation is one of the basic characteristics of PCV2 (Darwich et al, 2003a;Segalés et al, 2004;Stevenson et al, 2006;Darwich et al, 2008). Our study further confirmed this phenomenon.…”
Section: Discussionsupporting
confidence: 88%
“…Many studies have revealed that the induction of IL-10 upregulation is one of the basic characteristics of PCV2 (Darwich et al, 2003a;Segalés et al, 2004;Stevenson et al, 2006;Darwich et al, 2008). Our study further confirmed this phenomenon.…”
Section: Discussionsupporting
confidence: 88%
“…Previous studies (Darwich et al, 2003a, b;Hasslung et al, 2005;Stevenson et al, 2006) have shown that PCV2 may substantially alter unspecific cytokine responses and suggested that IL-10 might be one of the mechanisms by which these alterations take place. Based on these previous ex vivo and in vitro studies, the role of PCV2-induced IL-10 in immune disorders in PMWS could not be precisely determined.…”
mentioning
confidence: 97%
“…Also, elevated systemic IL-10 mRNA levels have been reported in PMWSaffected pigs (Sipos et al, 2004); however, contradictory results on IL-10 mRNA levels have been described elsewhere (Sipos et al, 2005). In a recent report, serum IL-10 was associated with PCV2-infected piglets that subsequently developed PMWS (Stevenson et al, 2006). Non-replicating PCV2 can persist in dendritic cells (DCs) without affecting myeloid DC differentiation or antigen uptake and presentation (Vincent et al, 2005).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, increased serum levels of APPs have been reported in pigs experimentally infected with porcine reproductive and respiratory syndrome (PRRS) virus, porcine circovirus type 2, different serotypes of Actinobacillus pleuropneumoniae and Streptococcus suis (Heegaard et al, 1998;Asai et al, 1999;Hulten et al, 2003;Diaz et al, 2005;Sorensen et al, 2006;Stevenson et al, 2006). Serum APPs also increase in pigs naturally infected with A. pleuropneumoniae and in field cases of a Yolanda Saco and Lorenzo Fraile equally contributed to this paper.…”
Section: Introductionmentioning
confidence: 95%